Tambaqui (Colossoma macropomum) in RAS Technology: Zootechnical, Hematological, Biochemical and Kn Profiles at Different Stocking Densities During the Initial Grow-Out Phase - Emilly Cordeiro Petillo; Aline da Cunha Ferreira; Christiane Patrícia Feitosa de Oliveira; Lian Valente Brandão; Thiago Marinho-Pereira; Bruno Adan Sagratzki Cavero (Aquaculture Journal)
The tambaqui (Colossoma macropomum) is Brazil’s most farmed native species, playing a crucial role in aquaculture. This study aimed to evaluate growth, hematological, biochemical, and body condition (Kn) parameters of tambaqui under two stocking densities in a recirculating aquaculture system (RAS). A total of 240 tambaqui (12.2 ± 4.1 g; 6.63 ± 0.73 cm) were distributed across six experimental units in two treatments (SD1 = 140 fish m−3; SD2 = 180 fish m−3) with three replicates. After 45 days, no significant differences were observed in water quality or zootechnical performance (p > 0.05), with final productivities of 8.64 ± 1.85 kg m3 and 9.46 ± 1.95 kg m3 for SD1 and SD2, respectively. Elevated plasma glucose, cholesterol, and triglyceride levels indicated energy reserve mobilization, suggesting some physiological response to higher stocking densities. However, other hematological and body condition parameters, including condition factor (Kn), indicated no significant adverse effects. These findings suggest that tambaqui can tolerate these stocking densities in RAS without compromising body condition, supporting the species’ intensive farming potential in controlled systems. This study highlights the importance of balancing productivity and physiological conditions in aquaculture management.